Pengelolaan Media Sosial Instagram @banksampahbersinar.id sebagai Media Komunikasi dan Informasi - Sari, Putri Puspita; Amin, Dang Eif Saeful; Maarif, Abdul Azis (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2022)
This study aims to describe the management of Instagram social media carried out by Bank Sampah Bersinar on Instagram @banksampahbersinar.id through Regina Luttrel's circular model of some . The method used in this research is descriptive method with data collection techniques through passive participatory observation, in-depth interviews, and documentation. The results showed that the management of Bank Sampah Bersinar's Instagram social media consisted of four stages. First, the share stage, which consists of media selection and audience determination, needs analysis, and building public trust. Second, the optimize stage (optimizing) the message by collaborating to disseminate information. Third, manage information consisting of social media monitoring and rapid response. Fourth, engage the public by collaborating with the community.